Distribution of the Extracellular Matrix in the Pararubral Area of the Rat. (1st December 2018) - Szarvas, Dóra; Gaál, Botond; Matesz, Clara; Rácz, Éva
Highlights: Each type of the condensed ECM is recognizable in the pararubral area. Characteristic perineuronal nets were only recognizable with WFA and aggrecan. Key PNN molecules, the hyaluronan and link protein, show moderate expression. ECM pattern may be associated to the unique function of the pararubral area in the visuomotor system. Abstract: Previously we described similarities and differences in the organization and molecular composition of an aggrecan based extracellular matrix (ECM) in three precerebellar nuclei, the inferior olive, the prepositus hypoglossi nucleus and the red nucleus of the rat associated with their specific cytoarchitecture, connection and function in the vestibular system. The aim of present study is to map the ECM pattern in a mesencephalic precerebellar nucleus, the pararubral area, which has a unique function among the precerebellar nuclei with its retinal connection and involvement in the circadian rhythm regulation. Using histochemistry and immunohistochemistry we have described for the first time the presence of major ECM components, the hyaluronan, aggrecan, versican, neurocan, brevican, tenascin-R (TN-R), and the HAPLN1 link protein in the pararubral area. The most common form of the aggrecan based ECM was the diffuse network in the neuropil, but each type of the condensed forms was also recognizable. Characteristic perineuronal nets (PNNs) were only recognizable with Wisteria floribunda agglutinin (WFA) and aggrecan staining around some of the medium-sized neurons, whereas the small cells were rarely surrounded by a weakly stained PNNs. The moderate expression of key molecules of PNN, the hyaluronan (HA) and HAPLN1 suggests that the lesser stability of ECM assembly around the pararubral neurons may allow quicker response to the modified neuronal activity and contributes to the high level of plasticity in the vestibular system.